2014
DOI: 10.1016/j.nano.2013.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale artificial antigen presenting cells for T cell immunotherapy

Abstract: Artificial antigen presenting cells (aAPC), which deliver stimulatory signals to cytotoxic lymphocytes, are a powerful tool for both adoptive and active immunotherapy. Thus far, aAPC have been synthesized by coupling T cell activating proteins such as CD3 or MHC-peptide to micron-sized beads. Nanoscale platforms have different trafficking and biophysical interaction properties and may allow development of new immunotherapeutic strategies. We therefore manufactured aAPC based on two types of nanoscale particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
135
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(137 citation statements)
references
References 53 publications
2
135
0
Order By: Relevance
“…For instance, the shape of PLGA microparticles has been found to directly impact CD8+ T cell responses, with stretched, ellipsoidal PLGA aAPCs decorated with anti-CD28 and MHC-IgG dimer improving CD8+ T-cell expansion by 2- to 20-fold, compared with spherical aAPCs (131). In addition, Perica et al have recently reported the development of nanoscale aAPCs synthesized from 50-100 nm iron-dextran paramagnetic particles and 30 nm quantum dot nanocrystals (132). Both nano-aAPC systems induced antigen specific T cell proliferation and functional responses in vitro (132), with iron-dextran paramagnetic particles even allowing magnetic field-induced T cell activation (133).…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the shape of PLGA microparticles has been found to directly impact CD8+ T cell responses, with stretched, ellipsoidal PLGA aAPCs decorated with anti-CD28 and MHC-IgG dimer improving CD8+ T-cell expansion by 2- to 20-fold, compared with spherical aAPCs (131). In addition, Perica et al have recently reported the development of nanoscale aAPCs synthesized from 50-100 nm iron-dextran paramagnetic particles and 30 nm quantum dot nanocrystals (132). Both nano-aAPC systems induced antigen specific T cell proliferation and functional responses in vitro (132), with iron-dextran paramagnetic particles even allowing magnetic field-induced T cell activation (133).…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…In addition, Perica et al have recently reported the development of nanoscale aAPCs synthesized from 50-100 nm iron-dextran paramagnetic particles and 30 nm quantum dot nanocrystals (132). Both nano-aAPC systems induced antigen specific T cell proliferation and functional responses in vitro (132), with iron-dextran paramagnetic particles even allowing magnetic field-induced T cell activation (133). Notably, when administered in vivo, nano-aAPCs effectively primed adoptively transferred CTLs to attenuate tumor growth in vivo .…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Micro-meter sized aAPC display limited lymphatic drainage(21) and are cleared and phagocytosed by professional phagocytes such as macrophages and immature DC(2224). Therefore, many efforts are made to generate optimal aAPC scaffolds that exhibit minimal systemic clearance and maximal in vivo functionality(11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shen et al have reported the successful in vivo usage of KaAPC utilizing 5 μm latex beads conjugated to anti-Fas (clone Jo2) and anti-His/H2-K b -TRP2 11 . We have been able to show that the general concept of artificial antigen-presenting Cells (aAPC) can be successfully transferred from μm sized to nm sized particles 12 and that functionality is influenced by particle geometry 13 . Thus, by varying the size and/or shape of future KaAPC designs one might be able to impact on the in vivo functionality and bio-distribution, which could be key for successful treatment of organ specific autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%